Shopee atau Tokopedia? Studi Perbedaan Tingkat Kepuasan Konsumen Belanja Online Pada Generasi Z di Kabupaten Majene - Rahmat Ghazali; Dian Rahmayanti Rivai; Nur Ariyandani; Irawati Irawati; Futri Ayu Wulandari (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
This study aims to analyze the differences in online shopping satisfaction among Generation Z in Majene regency by comparing two e-commerce platforms, Shopee and Tokopedia, based on three aspects: price, service quality, and delivery service. Data were collected through questionnaires distributed to respondents. The sampling technique employed was purposive sampling, and the sample size was determined using Roscoe’s rule of thumb, resulting in a total of 60 respondents. The collected data were analyzed using descriptive analysis and a paired sample t-test. The results indicate significant differences in satisfaction levels in terms of service quality and price, while no significant difference was found in the delivery service aspect between the two platforms Shopee and Tokopedia.